Eclectic Paradigm and the analysis of FDI in tourism in Nepal - Basnyat, Sandeep (The Gaze: Journal of Tourism and Hospitality, 2013)
This paper analyzes the factors that determine the inflows of FDI in tourism sector of Nepal using Eclectic Theory (Paradigm) propounded by John Dunning. It was observed that the first and second conditions (ownership specific advantages and internalization advantages) are firm specific determinants of FDI, whereas, the third is location-specific and, therefore, has a crucial influence on the host country Nepal’s inflows of FDI in tourism. It was further observed that the development impact of FDI on the tourism industry of Nepal may be determined by various combinations of three main important factors – policy environment, including policy reforms that trigger further inflows of FDI; the level of development (and maturity) of the tourism industry; and, the geography of Nepal. The paper suggests that MNC’s can help Nepal by, among other things, diversifying the supply of tourism products and improving the local service standards. The Gaze: Journal of Tourism and Hospitality Vol.5 2013 pp.69-82